Reasons and risk factors for hospitalization of new and previously diagnosed diabetes patients in tertiary health care center, Nepal. - Lamichhane, Pratik (2020)
ABSTRACT: Background: Diabetes mellitus is a chronic non-communicable disease that causes various complications requiring hospitalization of the patients. With insufficient diabetes management practice in Nepal, it poses a significant burden to the healthcare system of Nepal. A little information is available on hospitalization of diabetes patients and factors associated with hospital stay in Nepal. Aim: The aim was to identify the causes of admission of individual with diabetes and to identify the factors related to their hospitalization. Methods: This is a cross-sectional hospital-based study conducted from Bhadra 2077 to Poush 2077 on in-patients of Internal Medicine department of Tribhuwan University Teaching Hospital (TUTH). Patients aged ≥18 years who had received a diagnosis of diabetes mellitus were enrolled and followed through their hospital stay to collect data. Results: The three most frequent reasons of hospital admission of diabetes patients "Endocrine, nutritional and metabolic disorders", "Diseases of the circulatory system" and "Diseases of the nervous system". Chronic kidney disease was the most frequent unique diagnosis among the patients. Infections contributed to 27% of all the hospitalizations. Age, duration of diabetes and number of co-morbidities were significantly associated with the length of stay of the patients. Duration of diabetes and number of co-morbidities are the predictors of duration of hospital stay as identified by the study. Conclusion: Endocrine, nutritional and metabolic disorders was the most frequent reason for hospital admission at TUTH. Hospitals in Nepal should recognize significant burden placed on them by diabetes patients and should focus on prevention of acute and chronic complications to minimize the hospitalization rate. Proper management of co-morbidities can be crucial to decrease the length of hospital stay of diabetes patients. Keywords: Diabetes mellitus, Hospitalization, Length of stay, Reasons of hospitalizations